New insights into benzo[⍺]pyrene osteotoxicity in zebrafish - Tarasco, Marco (2021)
Persistent and ubiquitous organic pollutants, such as the polycyclic aromatic hydrocarbon benzo[⍺]pyrene (BaP), represent a major threat to aquatic organisms and human health. Beside some well-documented adverse effects on the development and reproduction of aquatic organisms, BaP was recently shown to affect fish bone formation and skeletal development through mechanisms that remain poorly understood. In this work, zebrafish bonerelated in vivo assays were used to evaluate the osteotoxic effects of BaP during bone development and regeneration. Acute exposure of zebrafish larvae to BaP from 3 to 6 days post-fertilization (dpf) induced a dosedependent reduction of the opercular bone size and a depletion of osteocalcin-positive cells, indicating an effect on osteoblast maturation. Chronic exposure of zebrafish larvae to BaP from 3 to 30 dpf affected the development of the axial skeleton and increased the incidence and severity of skeletal deformities. In young adults, BaP affected the mineralization of newly formed fin rays and scales, and impaired fin ray patterning and scale shape, through mechanisms that involve an imbalanced bone remodeling. Gene expression analyses indicated that BaP induced the activation of xenobiotic and metabolic pathways, while negatively impacting extracellular matrix formation and organization. Interestingly, BaP exposure positively regulated inflammation markers in larvae and increased the recruitment of neutrophils. A direct interaction between neutrophils and bone extracellular matrix or bone forming cells was observed in vivo, suggesting a role for neutrophils in the mechanisms underlying BaP osteotoxicity. Our work provides novel data on the cellular and molecular players involved in BaP osteotoxicity and brings new insights into a possible role for neutrophils in inflammatory bone reduction.